Evidence for reproductive senescence across ray-finned fishes: A review - Vrtílek, Milan; Žák, Jakub; Reichard, Martin (Frontiers in Ecology and Evolution, 2022)
The origin, incidence and consequences of reproductive senescence vary greatly across the tree of life. In vertebrates, research on reproductive senescence has been mainly focused on mammals and birds, demonstrating that its variation is largely linked to critical life history traits such as growth patterns, juvenile and adult mortality, and reproductive strategy. Fishes represent half of vertebrate taxonomic diversity and display remarkable variation in life history. Based on a thorough literature review, we summarize current evidence on reproductive senescence in ray-finned fishes (Actinopterygii). While survival and physiological senescence are acknowledged in fish, their potential age-related reproductive decline has often been disregarded due to the prevalence of indeterminate growth. We demonstrate that age-related reproductive decline is reported across fish phylogeny, environments and traits. An important point of our review is that the incidence of reproductive senescence in a species depends on both the number of studies for that species and coverage of its maximum lifespan by the study. Reproductive senescence was documented for one third of studied fish species, with females suffering age-related declines in reproductive traits less often than males or both parents combined. Neither parental care, nor migratory strategy corresponded with the occurrence of reproductive senescence in fish. The traits that were affected by reproductive senescence most often were sex-specific, with pre-mating and mating category of traits declining in females and sperm quality and quantity in males. We also demonstrate that reproductive senescence can be buffered by indeterminate growth. We provide rich evidence of reproductive senescence across ray-finned fishes, but we highlight that better data on age-related reproduction in fishes is needed.